PENDAMPINGAN PROGRAM PENGEMBANGAN EKOWISATA MANGROVE SIMANJA SEBAGAI DESTINASI WISATA DI DUSUN JAGAPATI KELURAHAN KUTAWARU CILACAP: SIMANJA MANGROVE ECOTOURISM DEVELOPMENT PROGRAM ASSISTANCE AS A TOURISM DESTINATION IN JAGAPATI VILLAGE KUTAWARU SUB-DISTRICT CILACAP - Oto Prasadi; Ilma Fadlilah; Nurlinda Ayu T.; Hanung Kurniawan; Riyan Rudi Saputra; Sugiana Putri Lestari; Ari Gunawan (JAMAS : Jurnal Abdi Masyarakat, 2023)
Jagapati Hamlet, which is located in Kutawaru Village, Central Cilacap District, Cilacap Regency, is a coastal area that has been developed into an ecotourism area, where tourism activities are responsible for unspoiled areas managed according to natural principles with the aim of enjoying natural beauty involving elements of education. The purpose of community service activities is to increase knowledge of the importance of mangrove ecosystems and improve skills in processing food made from mangroves in improving the quality of life of the people of Kutawaru Village. Using a participatory approach, counseling individually and in groups with lecture methods, forum group discussion, method and results demonstrations. The activities carried out are environmental preservation in the form of planting mangroves carried out by several stakeholders, mangrove management and institutional training. In carrying out the growth and development of an ecotourism has several components, both in the form of institutions, human resources, tourist sites, concepts or systems and products offered in the area. Human resources are the dominant component because ecotourism sustainability can work well when there is human resource empowerment, especially the people in the ecotourism area. One of them is the community empowerment model used in the tourism sector Community Based Tourism or community-based tourism. This model provides tourism in an area by involving the community in various stages carried out. With the innovations implemented, it is hoped that Jagapati will become one of the main tourist destination villages in the city of Cilacap.